COVID-19 and financial stability: Practice ahead of theory - Jing Yang; Hélène Desgagnes; Grzegorz Hałaj; Yaz Terajima (Bank of Canada, 2022)
The COVID-19 pandemic forced policy-makers to deploy a range of unprecedented measures to support the economy. In this discussion paper, we discuss the outcome of the economic measures implemented in the context of financial stability in Canada. We also present related challenging policy questions that are being tackled by staff at the Bank. These include the uneven impact of the pandemic on households' financial conditions and how it affects the transmission of policy, the challenges associated with setting banks' countercyclical capital buffers, detecting imbalances in a buoyant housing market, and policy coordination challenges.
Keywords: H3; H84; G21; E61; E58; 330; Coronavirus disease (COVID-19); Financial stability; Financial system regulation and policies